Moroccan Female Religious Agents : Old Practices and New Perspectives - Ouguir, Aziza (Women and Gender: The Middle East and the Islamic World, 2020)
In Moroccan Female Religious Agents: Old Practices and New Perspectives , Ouguir studies Moroccan female religious agents in particular historical women saints and Sufis, the way they constructed powerful saintly personalities that challenged the dominant conventional norms, and the way they are received by venerators and feminist Islamist activists of modern Morocco. Through hagiographic and oral narratives, Ouguir examines the techniques religious women followed to achieve ethical self-formation and strong religious personalities that promoted them to leadership. She also examined the venerators', murshidᾱt and Islamist feminists' reception of women saints in their discourses. Ouguir states convincingly that Moroccan religious women agents in both Morocco's past and present are to be highlighted for broader discourses on Muslim women and feminism.